ADIPONECTIN AND ATHEROSCLEROTIC REMODELLING OF CAROTID ARTERIES - O. P. Shevchenko; A. O. Shevchenko; E. V. Shin; M. V. Tulikov; Yu. S. Slesareva; L. M. Ginsburg (Российский кардиологический журнал)
The associations between adiponectin levels and atherosclerotic remodelling of carotid arteries were investigated in 50 patients with coronary heart disease. Among patients with increased adiponectin levels, carotid atherosclerosis was less severe (significantly lower mean values of total plaque volume), while arterial wall elasticity was higher (lower mean values of arterial stiffness, Icompl), compared to individuals with lower adiponectin concentrations.